Effects of Environmental Change on Travelers’ Sleep Health: Identifying Risk and Protective Factors - Xiong, Wei; Fan, Fang; Qi, Haiying (Frontiers in Psychology, 2020)
Objective. The aim of the manuscript is to predict the risk and protective factors for the differential effects of the environment on travelers' sleep health. Methods A sample of 505 travelers who stayed overnight in one of 28 hotels completed a sleep quality scale (SQS), a reduced scale of Morningness/Eveningness questionnaire (rMEQ), hotel customer satisfaction questionnaire (H-SCI). Results. Individuals who are a morning type(p=.002), have reduced sleep duration(p=.010) and sensitivity to sleep environment(p=.000) are most affected by environmental change. Interestingly, business travelers are most affected by sleep disturbances compared to leisure travelers and travelers who are more satisfied with hotels are less likely to experience insomnia in a new sleep environment(p=.000) and insomniacs are more likely to recover from insomnia during trip(p=.000). Conclusions. Environmental change has an inconsistent impact on the sleep health of different individuals. In a new sleep environment, the possible risk factors of sleep health include (1) morning type, (2) reduced sleep duration during trip, (3) sensitivity to the sleep environment, and (4) business stress while the possible protective factors are satisfaction with hotels. Possible factors of aiding in recovery from home insomnia include (1) evening type, and (2) higher satisfaction with the hotels.